Understanding level of gold dinar and ability of gold Dinar among Diploma Muamalat Part 5 students in UiTM Puncak Alam / Muhammad Amir Syahmi Mohd Sukeri - Mohd Sukeri, Muhammad Amir Syahmi (2019)
The gold dinar is a kind of currency used by the public. The gold dinar is also the currency used during the reign of Islam that began in the days of the Prophet and continued its use during other Islamic reigns. In addition, gold dinar has many uses that can be used by humans. Among them the function of gold dinar is as a means of exchange of commodities or tools used in the buying and selling process. Selling is an activity run by humans to complement their daily lives. In Islam, the sale and purchase have its own pillar and condition to make it a legitimate transaction in Islam. In addition, the gold dinar has other capabilities as a good currency indicator. This gold-based gold dinar has a stable and strong value. In today's modern world, the dollar is a currency used as a currency indicator for most countries and dollars is one of the world's most widely used currency today. But the dollar has no stable monetary value and can change. This will cause the economic and financial crisis to occur and may affect the economy of small countries. Therefore, there are efforts by Islamic countries to re-use the gold dinar as indicator because gold dinar has a more stable and stable value. The main objective of this study is to identify the level of knowledge among the 5th semester Muamalat students about the history of gold dinar and to identify the ability of gold Dinar as an indicator of national currency among the 5th semester Muamalat students. The method used in this study is a qualitative method using descriptive statistic. The findings of this study indicate that the level of understanding of the students is closely related to the background of the study. Based on this study, further studies are encouraged to further improve the quality of Islamic studies students.